2015
DOI: 10.1113/expphysiol.2014.084434
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial perilipin 3 and perilipin 5 protein content in rat skeletal muscle following endurance training and acute stimulated contraction

Abstract: New Findings r What is the central question of this study?The aim was to determine whether mitochondrial protein content of perilipin 3 (PLIN3) and perilipin 5 (PLIN5) is increased following endurance training and whether mitochondrial PLIN5 protein is increased to a greater extent in endurance-trained rats when compared with sedentary rats following acute contraction. r What is the main finding and its importance?Mitochondrial PLIN3 but not PLIN5 protein was increased in endurance-trained compared with sedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…With the use of the plantaris muscle, we were able to determine IMTG content and that there was an increase in stored muscle lipids with training and no inhibition of lipolysis (as witnessed by the delta of the rested vs. stimulated leg), despite the apparent increase in G0S2 content. Whereas there was not a significant increase in IMTG use, these data demonstrate that despite the increase in G0S2 content, there was no inhibition of lipolysis (32). This suggests that lipolysis is under more complex regulation by G0S2 and not simply by G0S2 content.…”
Section: R130mentioning
confidence: 57%
See 1 more Smart Citation
“…With the use of the plantaris muscle, we were able to determine IMTG content and that there was an increase in stored muscle lipids with training and no inhibition of lipolysis (as witnessed by the delta of the rested vs. stimulated leg), despite the apparent increase in G0S2 content. Whereas there was not a significant increase in IMTG use, these data demonstrate that despite the increase in G0S2 content, there was no inhibition of lipolysis (32). This suggests that lipolysis is under more complex regulation by G0S2 and not simply by G0S2 content.…”
Section: R130mentioning
confidence: 57%
“…Therefore, the purpose of our study was to characterize whole skeletal muscle and isolated mitochondrial G0S2 content in response to muscle contraction and endurance training in three skeletal muscles with varying oxidative capacities and metabolic profiles (SOL, RG, and WG). Our specific aims were the following: 1) to determine if endurance training would increase the capacity for lipolysis through alterations in muscle ATGL, CGI-58, and G0S2 protein content; 2) to determine if an acute, electrically stimulated contraction, which induced significant muscle lipolysis in whole muscle (30,32), would decrease G0S2 relative to ATGL and CGI-58 to regulate lipolysis acutely; and 3) to examine whether mitochondrial G0S2 content would increase with acute muscle contraction and endurance training to increase energy production.…”
mentioning
confidence: 99%
“…) and PLIN3 is observed in the mitochondrial fraction of sedentary and endurance‐trained rats (Ramos et al . ), suggesting that PLIN3 plays a role in IMTG oxidation. Taken together, these data suggest that redistributing PLIN2, PLIN3 and PLIN5 in response to acute FFA elevation would confer a metabolic advantage by maintaining a metabolically flexible intramuscular LD pool.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, PLIN3 levels in muscle biopsies from healthy patients are positively correlated with whole-body oxidative capacity, while PLIN3 knockdown results in decreased FA oxidation [81]. Subcellular localization of PLIN3 may play a role in its function, as it has been observed that endurance training, but not electrically induced contraction, induces PLIN3 expression and its association with mitochondria in rats (Figure 1(c)) [82]. Whether species-specific function or intracellular localization is responsible for this discrepancy is still unknown.…”
Section: Role Of Lipid Droplets and Perilipinsmentioning
confidence: 99%